2013 World Electric Vehicle Symposium and Exhibition (EVS27) 2013
DOI: 10.1109/evs.2013.6915040
|View full text |Cite
|
Sign up to set email alerts
|

An e.Bike design for the fourth generation bike-sharing services

Abstract: Bicycle sharing systems have proven their value towards urban sustainable mobility. Appropriate design of bikes for this application is fundamental for bike-sharing systems viability. A new e.Bike was designed for the specific application of bike-sharing. This bike model has a significant number of new features that improve the user experience through an adequate position of motor, as well as the addition of new functions such as the locking of the bike and rider safety. At the same time the reduction of numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…However, this model is better for physically disabled people who need to move from one location to another at a higher rate. e work in [7] discusses E-Bike architecture for the fourth generation. From this article, the deep analysis of the E-Bike was carried out based on their requirements applied for it.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model is better for physically disabled people who need to move from one location to another at a higher rate. e work in [7] discusses E-Bike architecture for the fourth generation. From this article, the deep analysis of the E-Bike was carried out based on their requirements applied for it.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, uma revisão da literatura sobre o tema foi conduzida para este trabalho e, com base na classificação dos estudos realizados sobre o tema proposta pelos autores anteriormente citados, 55 publicações identificadas foram divididas em cinco categorias: (i) balanceamento das bicicletas nas estações; (ii) projeto de modificações no sistema; (iii) análise do comportamento dos usuários, (iv) análise de dados de uso das bicicletas: e (v) análise da estrutura do sistema. Apenas uma publicação, que focou no desenvolvimento de uma bicicleta elétrica para uso em sistemas de compartilhamento (MEIRELES et al, 2013), não foi inclusa nas categorias.…”
Section: Sistemas De Compartilhamento De Bicicletasunclassified
“…First, the operator needs to concentrate on a reliable, simple, effective, sustainable yet profitable system. [39]. A recent study found that cost and regular motor fault were among the key barriers to the use of e-bikes, whereas low costs, light weight, longevity, and smart features were among the key incentives to use them.…”
Section: Introductionmentioning
confidence: 99%